Effect of Cultural Affiliation on Adjustment, Anxiety and Social Support - Sinha, Kumari Bharti (Journal of Advanced Research in Journalism & Mass Communication, 2019)
There is a great effect of cultural affiliation on adjustment, anxiety and social support. For this, this study was conducted on 100 Tribal and 100 Non-tribal undergraduate students of the college located at Ranchi and Patna respectively. The purpose of the study was to examine the effect of cultural affiliation on adjustment, anxiety and social support of the respondents. Three hypotheses were formulated : (i) the Tribal and Non-tribal respondents will differ significantly in terms of adjustment patterns. (ii) the Tribal and Non-tribal respondents will differ significantly in terms of anxiety. (iii) there will be a significant correlation among anxiety, adjustment and social support. For the purpose, Hindi Adaptation of Bell’s Adjustment Inventory by Mohsin and Shamshad, Sinha’s Manifest Anxiety Scale and Asthana’s and Verma’s Social Support Scale were used to measuring adjustment anxiety and social support of the respondents respectively. T-test and r-test were employed for analysis of the data. In the light of the results, all the three hypotheses were confirmed. Non-tribal respondents showed better adjustment, lesser anxiety and high social support as compared to their Tribal counterparts. Anxiety and adjustment were found negatively correlated. How to cite this article: Sinha KB. Effect of Cultural Affiliation on Adjustment, Anxiety and Social Support. J Adv Res Jrnl Mass Comm 2019; 6(4): 33-35. DOI: https://doi.org/10.24321/2395.3810.201911